Tingkat kerusakan Hama Boleng (Cylas sp.) pada Enam Kultivar Ubi Jalar asal Kabupaten Lombok Barat - Azizah, Aulia; Supeno, Bambang; Haryanto, Hery (SENTRI: Jurnal Riset Ilmiah, 2025)
The sweetpotato weevil (Cylas sp.) is one of the most damaging pests of sweet potato (Ipomoea batatas L.), and its presence requires further investigation. This pest causes severe damage to both the stems and tubers, which are the economically valuable parts of the plant. Symptoms of infestation include the presence of holes in the tubers and stems, accompanied by a foul odor. This study aimed to determine the level of damage caused by Cylas sp. in six sweet potato cultivars. The research used an experimental method with a field trial, designed using a Randomized Complete Block Design (RCBD), consisting of six sweet potato cultivar treatments (U): Lato-lato (U1), Cilembu (U2), Thailand (U3), Kentang (U4), Ase (U5), and Purple (U6). Each treatment was repeated four times. The results showed that the six cultivars did not differ significantly in their susceptibility to Cylas sp. infestation. The cultivars that tended to suffer the highest damage were Lato-lato (9.04%) and Thailand (8.75%), while the Cilembu cultivar (U2) showed the lowest damage (0%). The highest tuber weight per plant was produced by the Ase cultivar (U5), at 1.05 kg per plant, while the greatest number of tubers per plant was found in the Lato-lato cultivar (U1), with 6.44 tubers per plant. There was a negative correlation between damage intensity and tuber weight, with R² = 0.786. The Ase cultivar is recommended as a superior variety due to its good resistance and high tuber yield.